NO TITLE FOUNDNO TITLE FOUND. Issue 1 (1st April 2020) - Bowen, Siân
Navigating through three distinct sites of knowledge – the seventeenth-century treatise on Malabar's plants, Hortus Malabaricus; historical herbaria; and protected areas of remote forests and coastal regions of Kerala – the project will stimulate innovative modes of drawing through considerations relating to the collection and preservation of rare plants. Generating a distinctive body of artworks at world-leading plant science research facilities and in the bio-diverse South Indian rainforest, the research asks: can drawing represent the vulnerabilities and resilience of rare plants, not through illustration and gathering information by creating marks on a substrate, but as a material phenomenon that can generate new knowledge?